Ischaemia due to a vascular malformation causing focal myositis. (25th August 2014) - Alkhawajah, Nuha Marwan; Kiehl, Tim-Rasmus; Bril, Vera
Abstract : Focal myositis secondary to an intramuscular vascular malformation has rarely been reported in the literature. We describe a 21-year-old woman presenting with left thigh pain. Imaging of the thigh muscles showed a vascular malformation and muscle biopsy demonstrated focal changes diagnosed initially as myositis. Ischaemia is thought to be the responsible mechanism.